Quantification of the area and shunt volume of multiple, circular, and noncircular ventricular septal defects: A 2D/3D echocardiography comparison and real time 3D color Doppler feasibility determination study. Issue 1 (29th October 2017) - Tracy, Evan; Zhu, Meihua; Streiff, Cole; Sahn, David J.; Ashraf, Muhammad
Abstract : Background: Quantification of defect size and shunt flow is an important aspect of ventricular septal defect (VSD) evaluation. This study compared three‐dimensional echocardiography (3DE) with the current clinical standard two‐dimensional echocardiography (2DE) for quantifying defect area and tested the feasibility of real time 3D color Doppler echocardiography (RT3D‐CDE) for quantifying shunt volume of irregular shaped and multiple VSDs. Methods: Latex balloons were sutured into the ventricles of 32 freshly harvested porcine hearts and were connected with tubing placed in septal perforations. Tubing was varied in area (0.13–5.22 cm²), number (1–3), and shape (circle, oval, crescent, triangle). A pulsatile pump was used to pump "blood" through the VSD (LV to RV) at stroke volumes of 30–70 mL with a stroke rate of 60 bpm. Two‐dimensional echocardiography (2DE), 3DE, and RT3D‐CDE images were acquired from the right side of the phantom. Results: For circular VSDs, both 2DE and 3DE area measurements were consistent with the actual areas ( R ² = 0.98 vs 0.99). For noncircular/multiple VSDs, 3DE correlated with the actual area more closely than 2DE ( R ² = 0.99 vs 0.44). Shunt volumes obtained using RT3D‐CDE positively correlated with pumped stroke volumes ( R ² = 0.96). Conclusions: Three‐dimensional echocardiography (3DE) is a feasible method for determining VSD area and is more accurate than 2DE for evaluating the area of multiple or noncircular VSDs. Real‐time 3D color Doppler echocardiography (RT3D‐CDE) is a feasible method for quantifying the shunt volume of multiple or noncircular VSDs.